2012
DOI: 10.1093/annonc/mdr151
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of sorafenib in relapsed and unresectable high-grade osteosarcoma after failure of standard multimodal therapy: an Italian Sarcoma Group study

Abstract: Sorafenib demonstrated activity as a second- or third-line treatment in terms of PFS at 4 months with some unprecedented long-lasting responses. Sorafenib, the first targeted therapy showing activity in osteosarcoma patients, deserves further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
279
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(295 citation statements)
references
References 40 publications
13
279
0
3
Order By: Relevance
“…Unfortunately, none of these receptors represents a "clinicallyrelevant" target, likely because the biologic forces driving osteosarcoma progression do not succumb to a single hit. Recently, we reported that the multikinase inhibitor sorafenib negatively impacted osteosarcoma growth (6), but that the effect was brief (11). Surely, these considerations, make a compelling case to explore drug combinations to enhance sorafenib activity in sorafenib-based regimens that can be effectively translated into therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, none of these receptors represents a "clinicallyrelevant" target, likely because the biologic forces driving osteosarcoma progression do not succumb to a single hit. Recently, we reported that the multikinase inhibitor sorafenib negatively impacted osteosarcoma growth (6), but that the effect was brief (11). Surely, these considerations, make a compelling case to explore drug combinations to enhance sorafenib activity in sorafenib-based regimens that can be effectively translated into therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, sorafenib shows only minor activity in terms of temporary disease stabilization and slight tumor shrinkage in patients with advanced and unresectable osteosarcoma (11). Therefore, despite sorafenib activity, it is insufficient to halt osteosarcoma progression for both primary and secondary drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent reports have suggested the utility of sorafenib for the treatment of unresectable high-grade osteosarcoma, a malignancy where excess osteoid is produced by the malignant cells (Grignani et al 2012). Biochemical markers of bone turnover were not assessed in this study.…”
Section: Vegf Inhibitorsmentioning
confidence: 98%
“…Osteosarcoma therapy has been changed, at least in Europe, with the demonstration of the activity if mifurmatide in a phase III clinical trial (48,49), work that was propelled by translational research (50). A fraction of osteosarcomas respond to multitargeted tyrosine kinase inhibitors (51). Furthermore, pazopanib was approved in 2012 for use in patients with soft tissue sarcomas other than GIST or liposarcoma that are refractory to other systemic therapeutics (52).…”
Section: Challenges and Opportunities In Identifying Novel Agents Formentioning
confidence: 99%